Effect of drying conditions on the chemical compositions, molecular docking interactions and antioxidant activity of Hedychium spicatum Buch.-Ham. Rhizome essential oil - Aabha Gangwar; Geeta Tewari; Chitra Pande; Om Prakash; Bhawana Kanyal; Lalit M. Tewari; Manisha Joshi; Aysha Siddiqui (Scientific Reports)
Abstract The fresh and dried rhizomes of Hedychium spicatum are used to treat various ailments. The present work aimed to determine the influence of drying conditions (shade; HSSH, sun; HSS, oven; HSSV30 HSSV50, blower; HSB) on the essential oil profile and antioxidant potential of H. spicatum rhizomes. The oil was extracted by hydrodistillation method. The GC-FID and GC-MS were used to identify compounds, while the antioxidant potential was measured by DPPH radical scavenging, metal ion chelating and H2O2 scavenging methods. To investigate the inhibitory potential, molecular docking simulations were conducted on major compounds targeting NADPH oxidase. Drying significantly enhanced the oil yield of H. spicatum. The dominant compounds identified across all the samples were 1,8-cineole (14.62–53.87%), α-cadinol (10.62–25.06%), elemol (6.56–20.03%), germacrene-4-ol (3.73–11.27%), and α-muurolol (3.32–7.74%). The content of 1,8-cineole increased significantly while the percentage of elemol, germacrene-4-ol, α-muurolol, and α-cadinol decreased significantly in the dried rhizome samples. Among all the drying conditions, HSOV30 exhibited the highest oil yield, antioxidant potential and highest content of 1,8-cineole and elemol (marker components). Docking studies indicated that α-muurolol and α-cadinol exhibited favorable binding affinities and significant hydrophobic interactions with the enzyme’s active site, suggesting their efficacy. Therefore, the selection of the appropriate drying condition to obtain essential oils is important not only in terms of higher yield but also, most importantly, in terms of the percentage of compounds that can bring the essential oils to their sustainable use. It is the first report on the effect of drying on H. spicatum rhizomes.